Digital Constructions of Beauty: A Social Constructionist Study of Amanda Azahra on X - Alya Vania Rahma; Muhammad Fakhran al Ramadhan (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
This study explores the digital construction of beauty standards through the X account of Indonesian social media celebrity Amanda Azahra. The present study draws upon social constructionist theory (Berger and Luckmann), Stuart Hall's representation theory, and celebrity studies, in order to examine the manner in which beauty norms are produced, negotiated, and contested in Indonesian digital culture. Employing qualitative methods, namely content analysis, discourse analysis and cultural analysis, the research examined Azahra's most viral posts from 2023–2025, alongside audience responses and media coverage. Findings of this study indicate that the construction of beauty on social media is an interactive, contested, and culturally embedded process, rather than a unidirectional influence. Azahra's digital persona has been shown to reinforce and disrupt norms via strategic visual self-presentation, calibrated authenticity, and vulnerability branding. The audience's reactions to this phenomenon range from admiration and parasocial attachment to ironic objectification and critique. Three key framing mechanisms are identified: direct beauty attribute definitions, causal links between beauty efforts and positive outcomes, and associations with aspirational lifestyles. Present study contributes to the understanding of how social media reshapes beauty discourses, gendered identities, and evolving values in contemporary Indonesia, revealing tensions between traditional femininity and modern digital practices.